Effect of lattice mismatch on film morphology of the quasi-one dimensional conductor K0.3MoO3. Issue 8 (3rd February 2022) - Cao, Yifeng; Russo, Nicholas; Gao, Lei; Ji, Ailing; Doerrer, Linda H.; Lu, Nianpeng; Smith, Kevin E.
Abstract : High quality epitaxial thin films of the quasi-one dimensional conductor K0.3 MoO3 have been successfully grown on SrTiO3 (100), SrTiO3 (110), and SrTiO3 (510) substrates via pulsed laser deposition. Abstract : High quality epitaxial thin films of the quasi-one dimensional conductor K0.3 MoO3 have been successfully grown on SrTiO3 (100), SrTiO3 (110), and SrTiO3 (510) substrates via pulsed laser deposition. Scanning electron microscopy revealed quasi-one dimensional rod-shaped structures parallel to the substrate surface, and the crystal structure was verified by using X-ray diffraction. The temperature dependence of the resistivity for the K0.3 MoO3 thin films demonstrates a metal-to-semiconductor transition at about 180 K. Highly anisotropic resistivity was also observed for films grown on SrTiO3 (510).